Libyan EFL Teachers’ Perceptions of Teaching Competence: Towards Progress, Not Perfection - Elhaj, Iman A. (مجلة جامعة صبراتة العلمية, 2022)
This study aimed to identify Libyan EFL university teachers’ perceptions of teaching competence and the qualities of competent teachers. A qualitative research was used to investigate these perceptions, and to explore which competencies are involved in the teaching practices. The results revealed that not all participants have clear perceptions of teaching competencies. Most of them reported misconceptions of these competencies as reflected in their lack of integration of the three pillars of knowledge, skills, and attitude. The results also indicated that there is no clear distinction between teaching competencies and that social competence received more attention than educational, learning, and technical competencies. College teachers are highly encouraged to develop their teaching competences and therefore it is suggested to offer focused training courses as an effective strategy to develop teaching competencies.